Phase change microcapsule and its preparation method and application, polyurethane grouting reinforcement material
By using phase-change microcapsules with tertiary amine groups on the surface in the polyurethane grouting reinforcement material, the problem of excessive heat release during the material curing process is solved, and the effect of reducing reaction heat and improving mechanical properties is achieved.
Patent Information
- Application Number
- CN202311611318.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-29
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-11-29
AI Technical Summary
Polyurethane grouting reinforcement materials release a large amount of heat during the curing process, resulting in thermal decomposition of the material core, core burning and smoldering, affecting the performance and safety of the material.
Phase change microcapsules are used, and their surface contains multiple tertiary amine groups, which are combined with specific chain extenders and modified boron nitride nanosheets, and are used in polyurethane grouting and curing materials to reduce reaction heat and improve mechanical properties.
It effectively reduces the reaction heat of polyurethane grouting cured materials, improves the mechanical properties of the materials, reduces the risk of core burning and smoldering, and enhances safety.
Smart Images

Figure BDA0004576814460000071 
Figure BDA0004576814460000081 
Figure BDA0004576814460000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of phase change microcapsules, in particular to a phase change microcapsule and a preparation method and application thereof, and a polyurethane grouting reinforcement material. Background Art
[0002] Polyurethane (PU) grouting reinforcement materials are widely used in the construction and maintenance of civil engineering projects such as coal mines, high-speed railways, subways and tunnels. They have the characteristics of moderate slurry viscosity, adjustable setting time, high consolidated body strength and chemical corrosion resistance. After solidification, they form a network skeleton structure in the rock mass, which fundamentally changes the surrounding rock failure mechanism and improves the bearing capacity of the surrounding rock.
[0003] During the curing process of polyurethane grouting materials, the reaction between isocyanate and active hydroxyl compounds will release a lot of heat. At the same time, due to the low thermal conductivity of the solid body, it is difficult to release heat when used in large quantities in a confined space, which will cause thermal decomposition of the core of the material, leading to core burning and smoldering, causing material performance degradation, and producing obvious thermal effects on the surrounding environment, posing serious safety hazards.
[0004] Controllable regulation of the exothermic reaction of polyurethane grouting materials for engineering has been one of the hot issues in recent years. At present, inorganic fillers such as silica are often added, or organic resins such as epoxy resins are introduced into the system for modification, which can reduce the amount of isocyanate and active hydroxyl compounds per unit mass in the grouting material and reduce the exothermic heat of the curing reaction. However, the agglomeration of inorganic fillers will increase the viscosity of the slurry and affect the filling and compaction process of the slurry; the introduction of organic resins will reduce the compressive strength of the consolidated body, which is not conducive to the improvement of the residual strength of the rock mass after reinforcement. Summary of the invention
[0005] Based on the technical problems existing in the background technology, the present invention proposes a phase change microcapsule and its preparation method and application, a polyurethane grouting reinforcement material. The surface of the phase change microcapsule of the present invention contains multiple tertiary amine groups, which cooperate with specific chain extenders and modified boron nitride nanosheets and are used in polyurethane grouting curing materials. It has good reaction heat reduction performance and can improve the mechanical properties of the polyurethane grouting curing material.
[0006] The invention provides a phase-change microcapsule, comprising a core material and a wall material, wherein the wall material is polyurethane containing tertiary amine groups.
[0007] Preferably, the particle size of the phase change microcapsules is 4-21 μm.
[0008] Preferably, the core material is at least one of paraffin and octadecane.
[0009] Preferably, the polyurethane is obtained by reacting diisocyanate, polyamine, polyol, a chain extender containing a tertiary amine group, and a catalyst.
[0010] Preferably, the chain extender containing a tertiary amine group is N-methyldiethanolamine.
[0011] Preferably, the diisocyanate is at least one of hexamethylene diisocyanate, diphenylmethane diisocyanate, toluene diisocyanate and isophorone diisocyanate.
[0012] Preferably, the polyamine is polyethyleneimine 600.
[0013] Preferably, the polyol is at least one of glycerol and butanetriol.
[0014] The weight ratio of the core material to the diisocyanate is 2-5:1.
[0015] Preferably, the weight ratio of diisocyanate, polyamine, polyol, chain extender containing tertiary amine group, and catalyst is 1:0.15-0.2:0.25-0.3:0.1-0.15:0.03-0.07.
[0016] The present invention also proposes a method for preparing the above-mentioned phase change microcapsules, comprising the following steps: in an inert gas atmosphere, mixing the molten core material with diisocyanate as an oil phase, adding the oil phase dropwise into an aqueous solution containing a surfactant and mixing, then adding polyamine, polyol, a chain extender containing a tertiary amine group, and a catalyst to react to obtain phase change microcapsules.
[0017] The present invention first mixes the molten core material with diisocyanate so that the core material wraps the diisocyanate as the oil phase, then mixes it with an aqueous solution containing a surfactant, and then reacts with polyamines, polyols, and a chain extender containing a tertiary amine group to obtain a phase change microcapsule, so that the surface of the phase change microcapsule contains multiple tertiary amine groups.
[0018] Preferably, when the oil phase is added dropwise, the aqueous solution containing the surfactant is in a continuously stirred state.
[0019] Preferably, the rotation speed is 750-3000 rpm.
[0020] Selecting an appropriate stirring speed can produce phase change microcapsules with smaller particle size.
[0021] Preferably, the reaction temperature is 55-65° C., the reaction time is 1.5-2.5 h, and the reaction speed is 500-700 rpm.
[0022] Preferably, the surfactants are sodium dodecyl sulfate and Pluronic F127.
[0023] Preferably, the weight ratio of sodium dodecyl sulfate to Pluronic F127 is 1:0.8-1.2.
[0024] Preferably, the mass fraction of the aqueous solution containing the surfactant is 2.5-3.5 wt %.
[0025] Preferably, the weight ratio of diisocyanate to surfactant is 1:2.5-3.5.
[0026] The particle size of the phase change microcapsules can be further controlled by selecting a suitable surfactant and dosage; the above-mentioned Pluronic F127 can be purchased from BASF AG, Germany.
[0027] In the preparation method of the phase-change microcapsules, after the reaction, the temperature is lowered, the solid and liquid are separated, and the phase-change microcapsules are washed and dried to obtain the phase-change microcapsules.
[0028] The invention also proposes the application of the phase change microcapsule in polyurethane grouting reinforcement material.
[0029] The present invention also proposes a phase change microcapsule polyurethane grouting reinforcement material, the raw materials of which include: diisocyanate, polyol, chain extender, catalyst, thermal conductive filler, and the above-mentioned phase change microcapsule; wherein the chain extender is at least one of 2,2-dihydroxymethylpropionic acid and 2,2-dihydroxymethylbutyric acid.
[0030] Preferably, the thermally conductive filler is glycine-modified boron nitride nanosheets.
[0031] The present invention utilizes the tertiary amine groups in the phase change microcapsules to carry out electrostatic adsorption with the carboxyl groups in the chain extender and the heat conductive filler, so that the surface of the phase change microcapsules is coated with boron nitride nanosheets and multiple hydroxyl groups are introduced; then the polyurethane curing reaction is participated in, on the one hand, the multiple hydroxyl groups introduced react with the diisocyanate, so that the phase change microcapsules are connected to the polyurethane molecular chain, which can better absorb heat and reduce the reaction heat, and the boron nitride nanosheets can promote the heat transfer to the core material of the phase change microcapsules, further improving the heat reduction rate; on the other hand, the phase change microcapsules are connected to the polyurethane molecular chain, so that the phase change microcapsules are evenly distributed, and the multiple hydroxyl groups introduced can promote the mutual cross-linking of the polyurethane chains, improve the mechanical properties of the solid phase material, and in addition, the introduction of the boron nitride nanosheets can further improve the mechanical properties of the solid phase treatment.
[0032] The glycine-modified boron nitride nanosheets can be purchased from the market or prepared according to conventional methods in the art. For example, the preparation method can be: glycine, boron nitride and deionized water are mixed and ball-milled in an inert gas atmosphere to obtain glycine-modified boron nitride nanosheets.
[0033] Preferably, the weight ratio of the chain extender, the thermal conductive filler and the phase change microcapsule is 0.3-0.4:0.04-0.06:1.
[0034] Preferably, the content of phase change microcapsules in the phase change microcapsule polyurethane grouting reinforcement material is 2.5-10wt%.
[0035] By selecting the appropriate content of phase change microcapsules, the viscosity of the grouting can be controlled to meet the grouting requirements.
[0036] Preferably, the polyol is a polyether polyol.
[0037] Preferably, the polyether polyol is at least one of polyether polyol 4450 and polyether polyol N220.
[0038] Preferably, the diisocyanate is polyphenylpolymethylene polyisocyanate.
[0039] Preferably, the weight ratio of diisocyanate to polyol is 1:0.7-1.5.
[0040] Preferably, the weight ratio of diisocyanate to catalyst is 870-1010:1.
[0041] The catalyst may be dibutyltin dilaurate, etc. The phase change microcapsule polyurethane grouting reinforcement material may also contain auxiliary agents such as flame retardants and antioxidants.
[0042] The present invention also proposes a method for preparing the above-mentioned phase change microcapsule polyurethane grouting reinforcement material, comprising the following steps: mixing a thermal conductive filler, a chain extender, a phase change microcapsule and water, standing, separating the solid and the liquid, and drying to obtain an intermediate material; mixing a polyol, an intermediate material and a catalyst as material A; mixing material A and a diisocyanate, and curing to obtain a phase change microcapsule polyurethane grouting reinforcement material.
[0043] Preferably, the solvent of the chain extender solution is water.
[0044] Preferably, let stand for 1-2 hours.
[0045] Preferably, material A and diisocyanate are stored separately, and material A and diisocyanate are mixed and cured before use.
[0046] Beneficial effects:
[0047] 1. The present invention first mixes the molten core material with diisocyanate so that the core material wraps the diisocyanate as the oil phase, then mixes it with an aqueous solution containing a surfactant, and then reacts with polyamines, polyols, and a chain extender containing a tertiary amine group to obtain a phase change microcapsule, so that the surface of the phase change microcapsule contains multiple tertiary amine groups.
[0048] 2. The present invention utilizes the tertiary amine groups in the phase change microcapsules to electrostatically adsorb the carboxyl groups in the chain extender and the thermal conductive filler, so that the surface of the phase change microcapsules is coated with boron nitride nanosheets and multiple hydroxyl groups are introduced (i.e., the intermediate material).
[0049] 3. The intermediate material is involved in the polyurethane curing reaction. On the one hand, the introduced multiple hydroxyl groups react with diisocyanate to connect the phase change microcapsules to the polyurethane molecular chain, which can better absorb heat and reduce reaction heat. The boron nitride nanosheets can promote the transfer of heat to the core material of the phase change microcapsules, further increasing the rate of heat reduction. On the other hand, the phase change microcapsules are connected to the polyurethane molecular chain, so that the phase change microcapsules are evenly distributed. The introduced multiple hydroxyl groups can promote the mutual cross-linking of the polyurethane chains and improve the mechanical properties of the solid phase material. In addition, the introduction of boron nitride nanosheets can further improve the mechanical properties of the solid phase treatment. DETAILED DESCRIPTION
[0050] The technical solutions of the present invention are described in detail below through specific embodiments. However, it should be clearly stated that these embodiments are for illustration only and are not to be construed as limiting the scope of the present invention.
[0051] Source of raw materials:
[0052] Hexamethylene diisocyanate (AR, Shanghai Aladdin Biochemical Technology Co., Ltd.), polyethyleneimine 600 (AR, Shanghai Aladdin Biochemical Technology Co., Ltd.), propylene glycol (AR, Sinopharm Chemical Reagent Co., Ltd.), sodium dodecyl sulfate (AR, Woridas Experimental Reagents and Consumables), Pluronic F127 (AR, BASF SE, Germany), polyphenyl polymethylene polyisocyanate (industrial grade, BASF SE, Germany), polyether polyol 4450 (industrial grade, Hebei Yadong Chemical Group Co., Ltd.), polyether polyol N220 (industrial grade, Hongbaoli Group Co., Ltd.), dibutyltin dilaurate (AR, Shanghai Aladdin Biochemical Technology Co., Ltd.), and deionized water were homemade in the laboratory.
[0053] Test Method
[0054] Particle size test: The prepared phase change microcapsules were tested for particle size at room temperature using a dynamic laser particle size distribution analyzer (Nano-ZS90). Before the test, a phase change microcapsule solution with a concentration of 0.1 wt% was prepared using deionized water for the test.
[0055] Viscosity test: The slurry viscosity is measured using an LVDV-II+P digital viscometer in accordance with ASTM D1084-08. The test data results need to be between 60% and 80% of the range at the selected viscometer speed. Each group of samples is tested three times, and the three test results are averaged.
[0056] Mechanical properties test: The compression properties of polyurethane grouting reinforcement materials were tested using a CMT4101-SANS universal testing machine. According to the standard "AQ / T 1089-2020 Polymer Materials for Coal Mine Reinforcement of Coal Rock Mass", the samples were made into cylinders with a diameter of 50 mm and a height of 100 mm. The compression speed during measurement was 5 mm / min, and the calculation results were accurate to 1 MPa. Each group of samples was tested three times, and the average of the three test results was taken.
[0057] The tensile properties of polyurethane grouting reinforcement materials were tested using a CMT4101-SANS universal testing machine. Tensile specimens were prepared in accordance with GB / T2567-2008 Test Method for Performance of Resin Castings, and the test was performed at a tensile speed of 10 mm / min and a gauge length of 50 mm. The calculation results were accurate to 1 MPa, and each group of specimens was tested three times, and the average of the three test results was taken.
[0058] Curing temperature and curing time test: According to the standard "AQ / T 1089-2020 Polymer Materials for Coal Mine Reinforcement", use a digital display thermocouple to measure the curing reaction temperature of the sample. At 25±2℃, first mix the two components of the slurry and stir quickly. After mixing evenly, pour it into the test mold quickly. The mold has a diameter of 50mm and a height of 100mm. Then immediately insert the probe of the thermocouple thermometer into the center of the sample. Record the curing temperature and curing time data every 10s. Repeat the test three times for each group of samples, and take the average of the three test results.
[0059] Differential Scanning Calorimetry (DSC): The phase change behavior of the phase change microcapsules was tested using a differential scanning calorimeter, and the test sample gas was nitrogen. The sample was heated from -10°C to 60°C at a rate of 10°C / min and stabilized for 5 minutes to obtain a thermal behavior curve.
[0060] Thermal permeability test: The thermal permeability behavior of MEPCMs at 40°C was tested using a FLK Ti480 PRO infrared thermal imager, capturing and recording images every 20 seconds.
[0061] Examples 1-4
[0062] A phase-change microcapsule comprises a core material of paraffin and a wall material, wherein the wall material is polyurethane containing tertiary amine groups.
[0063] The preparation method of the phase change microcapsules comprises the following steps: under nitrogen protection, at 40°C, adding paraffin into a beaker to melt the paraffin, adding hexamethylene diisocyanate, stirring to make it uniformly mixed, and using it as an oil phase; then adding surfactants sodium dodecyl sulfonate and Pluronic F127 into deionized water, heating and stirring at 500 rpm for 10 minutes in a water bath at 40°C, then increasing the speed to 1500 rpm, then dropping the oil phase, maintaining the speed and stirring for 30 minutes, then adding a mixed solution of polyethyleneimine 600, glycerol, N-methyldiethanolamine, and dibutyltin dilaurate, heating to 60°C, reducing the speed to 600 rpm, and reacting for 2 hours; then cooling to room temperature, filtering, washing with deionized water and petroleum ether for at least three times, and drying to obtain phase change microcapsules.
[0064] The addition amount of each raw material in Examples 1-4 is shown in Table 1.
[0065] Table 1 Addition amount of each raw material in Examples 1-4
[0066]
[0067]
[0068] Note: The phase change microcapsules prepared in Examples 1-4 are respectively denoted as MEPCM-1, MEPCM-2, MEPCM-3, and MEPCM-4.
[0069] The phase change microcapsules prepared in Examples 1-4 were tested, and the results are shown in Table 2-3.
[0070] Table 2 Data corresponding to the DSC curves of the phase change microcapsules obtained in Examples 1-4
[0071] sample paraffin MEPCM-1 MEPCM-2 MEPCM-3 MEPCM-4 <![CDATA[ΔH m (J·g -1 )]]> 242.5 83.29 156.4 151.0 91.42 <![CDATA[T m (℃)]]> 18.8 28.69 30.01 30.05 29.14 Efficiency(%) 100.0 35.23 65.53 62.34 39.05
[0072] It can be seen from Table 2 that compared with paraffin, the endothermic peaks of the phase change microcapsules all move toward the high temperature direction. This is because the low thermal conductivity of the polyurethane shell of the phase change microcapsules affects the heat transfer. As the ratio of paraffin wax to hexamethylene diisocyanate decreases, the latent heat of the phase change microcapsules increases first and then decreases. This is because when the core material is more paraffin wax, the paraffin droplets cannot be fully and completely wrapped by the polyurethane wall material, and as the shell material increases, the paraffin wax is gradually completely wrapped by the polyurethane shell, and the latent heat increases accordingly; as the paraffin wax further decreases, the paraffin wax wrapped inside the microcapsule decreases, and the latent heat decreases.
[0073] The phase change microcapsules prepared in Examples 2-4 were placed on a relatively constant heating platform at 40°C, and a calibrated infrared camera was used to capture and record the evolution of the temperature distribution of the phase change microcapsules over time. The detailed data of the temperature change of the MEPCMs during heating to 180s as a function of heating time are shown in Table 3.
[0074] Table 3 Time required for the phase change microcapsules prepared in Examples 2-4 to be completely heated
[0075]
[0076] It can be seen from Table 3 that when the ratio of paraffin wax to hexamethylene diisocyanate is 4:1, MEPCM-2 has been completely heated at 183s, while MEPCM-3 and MEPCM-4 have not been completely heated. This shows that the thermal penetration of MEPCM-2 is faster than that of MEPCM-3 and MEPCM-4. It takes about 183s to be completely heated, while MEPCM-3 takes 220s and MEPCM-4 takes 238s. The heating rate of the phase change microcapsules increases with the decrease of the ratio of paraffin wax to hexamethylene diisocyanate. This is due to the gradual increase in its wall material affecting the heat transfer, which is consistent with the test results of DSC. Therefore, this delayed thermal response to ambient temperature is attributed to the latent heat absorption caused by the melting phase change of paraffin wax and the thermal buffering effect caused by the hindrance of the wall material. Combined with the thermal analysis results, MEPCM-2 has the best latent heat and thermal penetration behavior.
[0077] Example 5
[0078] The factors affecting the particle size of microcapsules include reaction temperature, rotation speed, emulsifier, etc., among which the rotation speed of the dispersion process has a greater impact on it. Keeping other conditions unchanged, according to the formula of Example 2, the rotation speed when the oil phase is added is adjusted to prepare phase change microcapsules, and the particle size of the phase change microcapsules prepared at different rotation speeds is tested. The results are shown in Table 4.
[0079] Table 4 Particle size results of phase change microcapsules obtained in Example 5
[0080]
[0081]
[0082] It can be seen from Table 4 that when the rotation speed is 1500rpm, the average particle size of the phase change microcapsules is 16.01μm, and when the rotation speed is 3000rpm, the particle size of the phase change microcapsules is 4.74μm; it can be seen that when the rotation speed during dispersion is higher, the particle size of the phase change microcapsules is smaller. This is because at high rotation speeds, the oil phase will form smaller and more uniform droplets, thereby obtaining microcapsules with smaller particle sizes. However, as the rotation speed is further increased, the encapsulation structure of the phase change microcapsules will be destroyed, resulting in paraffin seepage and affecting the grouting effect. Microcapsules with low particle sizes are easy to disperse in the slurry, ensuring the injectability of the grouting material. The phase change microcapsules prepared at a rotation speed of 1500rpm have both lower particle sizes and better encapsulation effects.
[0083] Embodiment 6-10
[0084] A phase-change microcapsule polyurethane grouting reinforcement material, the raw materials of which include: polyphenyl polymethylene polyisocyanate, polyether polyol 4450, polyether polyol N220, 2,2-dihydroxymethyl propionic acid, dibutyltin dilaurate, glycine-modified boron nitride nanosheets, and MEPCM-2 (phase-change microcapsules prepared in Example 2).
[0085] The preparation method of the above-mentioned phase change microcapsule polyurethane grouting reinforcement material comprises the following steps:
[0086] 0.1 g of boron nitride, 0.3 g of glycine and 2 ml of deionized water were ultrasonically dispersed uniformly, transferred to a ball mill, and ball-milled at 500 rpm for 12 h under nitrogen protection. The supernatant was centrifuged and vacuum filtered, washed with water and ethanol for 3 times, dried, and ground to obtain glycine-modified boron nitride nanosheets.
[0087] The aqueous dispersion of glycine-modified boron nitride nanosheets and MEPCM-2 were stirred for 30 minutes to mix evenly, and then 2,2-dihydroxymethylpropionic acid aqueous solution was added and stirred for 30 minutes to mix evenly, and the mixture was allowed to stand at room temperature for 2 hours, filtered, washed with water 3 times, and dried to obtain an intermediate material;
[0088] At 110°C and under the condition of vacuum pump decompression to -0.1MPa, polyether polyol 4450 and polyether polyol N220 were dehydrated for 2h, cooled to room temperature, added with intermediate material and dibutyltin dilaurate, and stirred at 1000rpm to obtain material A (in slurry); material A was mixed with polyphenyl polymethylene polyisocyanate, stirred at 2000rpm for 30s, and then quickly poured into a polyvinyl chloride mold, and the slurry was changed from liquid to solid, and the curing reaction was completed to obtain a phase change microcapsule polyurethane grouting reinforcement material, and then the reinforcement material was taken out from the mold, left to mature at room temperature for 3 days, and the mechanical properties and maximum reaction temperature were tested. The amount of each raw material used in Examples 6-10 is shown in Table 5.
[0089] Table 5 Amount of each raw material used in Examples 6-10
[0090]
[0091] Note: The polyurethane grouting reinforcement materials prepared in Examples 6-10 are respectively recorded as PU, PU-2.5, PU-5, PU-7.5, and PU-10.
[0092] The slurry viscosity of polyurethane grouting solid material is one of the important indicators that affect the actual application effect of grouting materials. The addition of MEPCM-2 will have a certain impact on the slurry fluidity of material A. The slurry viscosity of material A in Examples 6-10 was investigated, and the results are shown in Table 6.
[0093] Table 6 Slurry viscosity results of material A in Examples 6-10
[0094] Grouping PU PU-2.5 PU-5 PU-7.5 PU-10 Slurry viscosity of material A (mPa·s) 312.5 368.1 446.2 549.3 668.2
[0095] It can be seen from Table 6 that when no phase change microcapsules are added (ie, Example 6), the slurry viscosity of material A is 312.5 mPa·s, and the slurry viscosities of material A in Examples 7-10 are 368.1, 446.2, 549.3, and 668.2 mPa·s, respectively; the slurry viscosity of material A gradually increases with the increase of the content of phase change microcapsules. This is because the number of insoluble particles in the solution increases and the surface energy of the phase change microcapsules is large, resulting in the slurry viscosity increasing with the increase of the content of phase change microcapsules.
[0096] The curing time and curing temperature are important indicators that affect the safety of the polyurethane grouting reinforcement material. The curing time and curing exothermic temperature of the polyurethane grouting reinforcement materials of Examples 6-10 were tested, and the results are shown in Table 7.
[0097] Table 7 Results of curing time and curing exothermic temperature of polyurethane grouting reinforcement materials of Examples 6-10
[0098] Grouping Curing time(s) Curing exotherm temperature (℃) PU 91 122.2 PU-2.5 151 110.2 PU-5 197 104.5 PU-7.5 240 96.2 PU-10 256 94.1
[0099] It can be seen from Table 7 that when phase change microcapsules are not added (i.e., Example 6), the curing time of polyurethane grouting is short, the maximum curing exothermic temperature is high, and the curing is rapid, which is not conducive to safe operation during actual grouting; as the content of phase change microcapsules increases, the curing time is prolonged and the maximum curing exothermic temperature decreases. It can be seen that the addition of phase change microcapsules can prolong the curing time of polyurethane reinforcement materials and reduce the maximum curing exothermic temperature. On the one hand, this is because the phase change microcapsules contain phase-changeable material paraffin, which is solid at room temperature. When the temperature rises during the curing stage of the material, part of the heat will be absorbed by the phase change microcapsules and a solid-liquid phase transition will occur, resulting in a slower temperature rise in the early stage of the curing reaction, which prolongs the curing time and reduces the curing exothermic rate. The heat released by the curing reaction can be transferred more to the external environment, thereby reducing the maximum curing exothermic temperature of the system.
[0100] Comparative Examples 1-3
[0101] Without adding 2,2-dihydroxymethylpropionic acid and glycine-modified boron nitride nanosheets, a polyurethane grouting reinforcement material was prepared according to the method of Example 9, which is recorded as Comparative Example 1.
[0102] Without adding glycine-modified boron nitride nanosheets, a polyurethane grouting reinforcement material was prepared according to the method of Example 9, which is recorded as Comparative Example 2.
[0103] Without adding 2,2-dimethylolpropionic acid, a polyurethane grouting reinforcement material was prepared according to the method of Example 9, which is recorded as Comparative Example 3.
[0104] The mechanical properties of Examples 6-10 and Comparative Examples 1-3 were tested, and the results are shown in Table 8.
[0105] Table 8 Mechanical properties test results of Examples 6-10 and Comparative Examples 1-3
[0106] Grouping Compressive strength(MPa) Tensile strength(MPa) Elongation at break (%) Example 6 52.1 18.2 406.4 Example 7 56.6 20.5 381.7 Example 8 59.2 22.8 360.3 Example 9 60.1 23.1 351.1 Example 10 56.0 20.2 392.5 Comparative Example 1 44.5 14.0 520.3 Comparative Example 2 59.9 23.0 349.8 Comparative Example 3 44.6 14.1 535.4
[0107] Comparing Example 6 with Examples 7-10, it can be seen that the mechanical properties of the polyurethane grouting reinforcement material can be improved by using 2,2-dihydroxymethylpropionic acid and glycine-modified boron nitride nanosheets in combination with phase change microcapsules, and the mechanical properties of Examples 7-10 are significantly better than those of Comparative Examples 1-3.
[0108] By comparing the results of Example 9 and Comparative Examples 1-3, it can be seen that the mechanical properties of the boron nitride nanosheets modified by 2,2-dihydroxymethylpropionic acid and glycine and the phase change microcapsules are better than those of Comparative Examples 1-3.
[0109] The curing time and curing exothermic temperature of the polyurethane grouting reinforcement materials of Comparative Examples 1-3 were tested, and the results are shown in Table 9.
[0110] Table 9 Results of curing time and curing exothermic temperature of polyurethane grouting reinforcement materials of comparative examples 1-3
[0111]
[0112]
[0113] Comparing Table 7 and Table 9, it can be seen that the use of phase change microcapsules alone, or the use of 2,2-dihydroxymethylpropionic acid or glycine modified boron nitride nanosheets in combination with phase change microcapsules, can prolong the curing time and reduce the curing exothermic temperature, but it is far lower than the effect of 2,2-dihydroxymethylpropionic acid, glycine modified boron nitride nanosheets and phase change microcapsules in combination.
[0114] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A phase change microcapsule polyurethane grouting reinforcement material, characterized in that: The raw materials include: diisocyanate 1, polyol 1, chain extender 1, catalyst 1, thermal conductive filler, and phase change microcapsules; wherein the chain extender 1 is at least one of 2,2-dihydroxymethyl propionic acid and 2,2-dihydroxymethyl butyric acid; The phase-change microcapsule comprises: a core material and a wall material, wherein the wall material is a polyurethane containing a tertiary amine group; The core material is at least one of paraffin and octadecane; The thermal conductive filler is glycine-modified boron nitride nanosheets; The weight ratio of chain extender 1, thermal conductive filler and phase change microcapsule is 0.3-0.4:0.04-0.06:1; In the phase change microcapsule polyurethane grouting reinforcement material, the content of phase change microcapsules is 2.5-10wt%; The weight ratio of diisocyanate 1 to polyol 1 is 1:0.7-1.5; The weight ratio of diisocyanate 1 to catalyst 1 is 870-1010:
1.
2. The phase change microcapsule polyurethane grouting reinforcement material according to claim 1, characterized in that: The particle size of the phase change microcapsules is 4-21 μm.
3. The phase change microcapsule polyurethane grouting reinforcement material according to claim 1, characterized in that: The wall material is obtained by reacting diisocyanate 2, polyamine, polyol 2, a chain extender containing a tertiary amine group, and a catalyst 2.
4. The phase change microcapsule polyurethane grouting reinforcement material according to claim 3 is characterized in that: The chain extender containing a tertiary amine group is N-methyldiethanolamine.
5. The phase change microcapsule polyurethane grouting reinforcement material according to claim 3, characterized in that: The diisocyanate 2 is at least one of hexamethylene diisocyanate, diphenylmethane diisocyanate, toluene diisocyanate, and isophorone diisocyanate.
6. The phase-change microcapsule polyurethane grouting reinforcement material according to claim 3, characterized in that: The polyamine was polyethyleneimine 600.
7. The phase-change microcapsule polyurethane grouting reinforcement material according to claim 3, characterized in that: The polyol 2 is at least one of glycerol and butanetriol.
8. The phase change microcapsule according to claim 3, characterized in that: The weight ratio of the core material to the diisocyanate 2 is 2-5:
1.
9. The phase-change microcapsule polyurethane grouting reinforcement material according to claim 3, characterized in that: The weight ratio of diisocyanate 2, polyamine, polyol 2, chain extender containing tertiary amine group and catalyst 2 is 1:0.15-0.2:0.25-0.3:0.1-0.15:0.03-0.
07.
10. The phase-change microcapsule polyurethane grouting reinforcement material according to claim 1, characterized in that: The preparation method of the phase change microcapsule comprises the following steps: in an inert gas atmosphere, the molten core material is mixed with diisocyanate 2 as an oil phase, the oil phase is added dropwise to an aqueous solution containing a surfactant and mixed, and then polyamine, polyol 2, a chain extender containing a tertiary amine group, and a catalyst 2 are added to react to obtain a phase change microcapsule.
11. The phase-change microcapsule polyurethane grouting reinforcement material according to claim 10, characterized in that: When the oil phase is added dropwise, the aqueous solution containing the surfactant is continuously stirred.
12. The phase-change microcapsule polyurethane grouting reinforcement material according to claim 11, characterized in that: The rotation speed is 750-3000rpm.
13. The phase-change microcapsule polyurethane grouting reinforcement material according to claim 10, characterized in that: The reaction temperature is 55-65°C, the reaction time is 1.5-2.5h, and the reaction speed is 500-700rpm.
14. The phase-change microcapsule polyurethane grouting reinforcement material according to claim 10, characterized in that: The surfactants were sodium dodecyl sulfate and Pluronic F127.
15. The phase-change microcapsule polyurethane grouting reinforcement material according to claim 14, characterized in that: The weight ratio of sodium dodecyl sulfate to Pluronic F127 is 1:0.8-1.
2.
16. The phase-change microcapsule polyurethane grouting reinforcement material according to claim 10, characterized in that: The mass fraction of the aqueous solution containing the surfactant is 2.5-3.5wt%.
17. The phase-change microcapsule polyurethane grouting reinforcement material according to claim 10, characterized in that: The weight ratio of diisocyanate 2 to surfactant is 1:2.5-3.
5.
18. The phase-change microcapsule polyurethane grouting reinforcement material according to claim 1, characterized in that: Polyol 1 is a polyether polyol.
19. The phase-change microcapsule polyurethane grouting reinforcement material according to claim 18, characterized in that: The polyether polyol is at least one of polyether polyol 4450 and polyether polyol N220.
20. The phase-change microcapsule polyurethane grouting reinforcement material according to claim 1, characterized in that: Diisocyanate 1 is polyphenylpolymethylene polyisocyanate.
21. A method for preparing the phase-change microcapsule polyurethane grouting reinforcement material according to any one of claims 1 to 20, characterized in that: The method comprises the following steps: mixing a thermal conductive filler, a chain extender 1, a phase change microcapsule and water, standing, separating the solid and the liquid, and drying to obtain an intermediate material; mixing a polyol 1, an intermediate material and a catalyst 1 to obtain an A material; and mixing the A material and a diisocyanate 1, and curing to obtain a phase change microcapsule polyurethane grouting reinforcement material.
22. The method for preparing the phase-change microcapsule polyurethane grouting reinforcement material according to claim 21, characterized in that: Let stand for 1-2 hours.
23. The method for preparing the phase-change microcapsule polyurethane grouting reinforcement material according to claim 21, characterized in that: Material A and diisocyanate 1 are stored separately and mixed evenly before use.
Citation Information
Patent Citations
Preparation method of phase change microcapsule with polyurethane wall material
CN109126653A
Microcapsule type phase change energy storage material as well as preparation method and application thereof
CN115253940A